Elevated CA-125 as Humoral Biomarker of Congestive Heart Failure: Illustrative Cases and a Short Review of Literature. (26th May 2020) - Frigy, Attila; Belényi, Boglárka; Kirchmaier, Ádám; Fekete, Nándor; Szabó, István Adorján
Abstract : Despite the recent, remarkable achievements in cardiology, heart failure (HF) remains a major public health problem due to its increasing prevalence, frequent hospitalizations, and significant mortality. Humoral biomarkers in HF are capable to reflect different aspects of the cardiac morpho-functional changes and the related pathophysiological processes and could have important diagnostic, prognostic, and therapeutical roles. CA-125 is a well-known tumor marker (mainly for ovarian cancer), and also a useful, but less applied cardiac biomarker. Practical aspects, possible pitfalls related with increased CA-125 levels are illustrated by two cases, both with HF, with the biomarker determined for other reasons and having high levels in the context of the cardiac decompensation. The paper presents a short review of the main biochemical, pathophysiological, and clinical data linked to CA-125, with special accent on its utility in patients with HF.